1,2,4-Triamino-5-nitrobenzene as air-stable aromatic polyamines for coordination chemistry - Pascal, Simon; Zaborova, Elena; Siri, Olivier (Comptes Rendus. Chimie)
We report the synthesis and characterization of two nickel complexes 7 and 8 based on 1,2,4-triamino-5-nitrobenzene 6. The formation of these compounds is observed from the same precursor, their stoichiometry depending on the nature of the solvent used for the crystallization. The key role of the nitro group in 6 is discussed, demonstrating its major impact on the stability and reactivity of the ligand. Each nickel complex could be characterized by single crystal X-ray analysis, highlighting the importance of the intramolecular H-bonding interactions on the stability of the complexes incorporating a monodentate aromatic amine-type ligand.